UNLOCKING THE POTENTIAL OF GEOAI: A PATH TO ADDRESSING GLOBAL CHALLENGES ACROSS MULTIPLE DISCIPLINES - Borase, Sudhakar J.; Baviskar, Sandesh R.; Nigale, Chintaman B.; Shendge, Laxman S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
he idea of Stan Openshaw and Christine Openshaw “ Let the data speak for themselves” is vision of progress as the human predictions and analytical work is to be done by data collected itself “ the data should speak by itself” with factor of artificial intelligence (A.I). The research aims to create an account of evolution and development in the field of geographic prediction and analysis. The research revolves around the development of artificial intelligence in the geography and its integration process . The field of geography and its interdisciplinary have a dynamic strategy and endured scope of development and how it will affect the current world , settlement , human occupation and specially in the field of economics which directly show its dynamic change on human living and environment balance. The applicable changes in Health sector, Mapping and Cartography, Research work, Environment epidemiology, Urban planning , Resource management , Fluid resource distribution , Population distribution and Environment science are presented here with an account of statement of geographer from various sources like journals, research paper and conference proceedings and statements. The engineering scope and geographic background are going to discuss together the futuristic infrastructure and co-operative institute with ideas presented by each other to maintain a prosperous Environment.